Wykorzystanie analizy dyskryminacyjnej do oceny różnic w rozwoju społecznym państw - Grześkowiak, Alicja (Application of discriminant analysis to evaluation of differences in social development of countries, 2005)
In this paper the application of descriptive discriminant analysis to evaluation of differences among countries with high, medium and low human development index is presented. Some variables connected with the demographic trends, health care and the access to information technologies were used to construct canonical discriminant functions. The quality of the derived functions was examined.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 239-249